2005
DOI: 10.1177/0363546504268406
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation after Anterior Cruciate Ligament Reconstruction: A Prospective, Randomized, Double-Blind Comparison of Programs Administered over 2 Different Time Intervals

Abstract: Anterior cruciate ligament reconstruction with a bone-patellar tendon-bone graft followed by either accelerated or nonaccelerated rehabilitation produces the same increase of anterior knee laxity. Both programs had the same effect in terms of clinical assessment, patient satisfaction, functional performance, and the biomarkers of articular cartilage metabolism. There is concern that the cartilage biomarkers remained elevated for an extended period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
151
1
9

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(166 citation statements)
references
References 41 publications
5
151
1
9
Order By: Relevance
“…They observed that patients who were non-compliant with earlier restrictive rehabilitation protocols, and who progressed as they felt comfortable, did in fact progress more rapidly, and regained their function more quickly, without any deleterious effects. In a subsequent randomised controlled trial, Beynnon et al compared accelerated and non-accelerated rehabilitation protocols, again in patients who had undergone ACL reconstruction with a patellar tendon graft [7]. Although they did not investigate return to sport per se, Tegner activity levels did not differ between the two groups and no deleterious effects of the accelerated protocol were identified.…”
Section: Discussionmentioning
confidence: 99%
“…They observed that patients who were non-compliant with earlier restrictive rehabilitation protocols, and who progressed as they felt comfortable, did in fact progress more rapidly, and regained their function more quickly, without any deleterious effects. In a subsequent randomised controlled trial, Beynnon et al compared accelerated and non-accelerated rehabilitation protocols, again in patients who had undergone ACL reconstruction with a patellar tendon graft [7]. Although they did not investigate return to sport per se, Tegner activity levels did not differ between the two groups and no deleterious effects of the accelerated protocol were identified.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors recommended patients need 4 to 6 months of rehabilitation before returning to sport activities after ACL reconstruction surgery and 6 to 9 months before returning to vigorous cutting and pivoting activities [5,12,15]. Although the majority of injured athletes are able to return to preinjury competition levels after rehabilitation, their performances may be adversely affected [7].…”
Section: Introductionmentioning
confidence: 99%
“…Presently, active early rehabilitation is believed to be the standard postoperative protocol. 4 The primary objective of rehabilitation following ACL reconstruction surgery is to restore knee function by increasing neuromuscular control. Currently, however, there is debate over various aspects of the most beneficial type of postoperative ACL rehabilitation program.…”
Section: Introductionmentioning
confidence: 99%